THE EFFECT ANALYSIS OF MOTIVATION, COMPETENCE AND ORGANIZATIONAL CULTURE ON EMPLOYEES PERFORMANCE OF JAKARTA SOCIAL DEPARTMENT - Finatariani, Endah (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
All this time, government institutions are still overshadowed by stigma, the poor performance of civil servants. Therefore, this research was conducted to analyze the influence of performance factors, including motivation, competence and organizational culture. This study uses a quantitative approach, causal associative research methods, descriptive and inferential analysis. The total population is 50 respondents, the sample technique used in the census and the analysis method uses multiple linear regression. The results of the analysis show that motivation, competence and organizational culture both partially and simultaneously have a significant effect on performance